2007
DOI: 10.1007/s00122-007-0537-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic patterns in rapeseed (Brassica napus L.): I. Crosses between spring and Chinese semi-winter lines

Abstract: Chinese semi-winter rapeseed is genetically diverse from Canadian and European spring rapeseed. This study was conducted to evaluate the potential of semi-winter rapeseed for spring rapeseed hybrid breeding, to assess the genetic effects involved, and to estimate the correlation of parental genetic distance (GD) with hybrid performance, heterosis, general combining ability (GCA) and specific combining ability (SCA) in crosses between spring and semi-winter rapeseed lines. Four spring male sterile lines from Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 39 publications
13
62
0
Order By: Relevance
“…Introgression between the comparatively diverse genetic pools of winter, semiwinter, and spring forms, however, may make it possible to exploit heterosis. For instance, Qian et al (2007) showed high heterosis for seed yield in hybrids between Chinese semiwinter pollinators and spring-type mother lines from Europe and Canada. Improvement of spring-type B. napus through the introgression of winter-type variability was also assessed by Kebede et al (2010), who demonstrated the heterosis effect of spring × winter doubled haploid lines over their parental lines.…”
Section: Taking Advantage Of Heterosismentioning
confidence: 99%
See 2 more Smart Citations
“…Introgression between the comparatively diverse genetic pools of winter, semiwinter, and spring forms, however, may make it possible to exploit heterosis. For instance, Qian et al (2007) showed high heterosis for seed yield in hybrids between Chinese semiwinter pollinators and spring-type mother lines from Europe and Canada. Improvement of spring-type B. napus through the introgression of winter-type variability was also assessed by Kebede et al (2010), who demonstrated the heterosis effect of spring × winter doubled haploid lines over their parental lines.…”
Section: Taking Advantage Of Heterosismentioning
confidence: 99%
“…Improvement of spring-type B. napus through the introgression of winter-type variability was also assessed by Kebede et al (2010), who demonstrated the heterosis effect of spring × winter doubled haploid lines over their parental lines. To avoid incompatibilities in developmental timing between these potential heterotic groups, Qian et al (2007) suggested that the genetic material should first be adapted to the local environment before being hybridized. It should be noted that the genetic distance between heterotic groups, commonly used to determine the hybridization scheme, is often not correlated with the hybrids' performance.…”
Section: Taking Advantage Of Heterosismentioning
confidence: 99%
See 1 more Smart Citation
“…Quijada et al (2006) identified quantitative trait locus (QTL) alleles of winter cultivars that increase seed yield in spring B. napus test hybrids. Qian et al (2007Qian et al ( , 2009 suggested that some of the alleles in Chinese semi-winter type, likely introgressed from B. rapa L., might contribute to high levels of heterosis for seed yield in both spring and winter B. napus hybrids.…”
mentioning
confidence: 99%
“…Thus, most of the studies conducted to date to evaluate different gene pools of Brassica for the improvement of spring or winter or semi-winter B. napus were focused on either the use of spring B. napus for spring type hybrid (Grant and Beversdorf, 1985;Brandle and McVetty, 1990;Engqvist and Becker, 1991;Diers et al, 1996;Cuthbert et al, 2009), or the use of winter or semi-winter B. napus for spring type hybrid (Butruille et al, 1999;Udall et al, 2004;Quijada et al, 2004Quijada et al, , 2006Qian et al, 2007;Kramer et al, 2009), or the use of winter or semi-winter B. napus for winter type hybrid (Lefort-Buson et al, 1987;Qian et al, 2009), or the use of the allied species for winter or semiwinter (Gehringer et al, 2007;Radoev et al, 2008;Zou et al, 2010;Fu et al, 2012;Girke et al, 2012;Li et al, 2014) or spring Seyis et al, 2006) type of hybrid. However, so far, no study has been conducted to compare the value of different gene pools for increasing the level of heterosis and seed yield in spring B. napus hybrid canola.…”
mentioning
confidence: 99%